Transcription and Remodeling Produce Asymmetrically Unwrapped Nucleosomal Intermediates. - Ramachandran, S.; Ahmad, K.; Henikoff, S. (Molecular Cell, 2017)
Nucleosomes are disrupted during transcription and other active processes, but the structural intermediates during nucleosome disruption in vivo are unknown. To identify intermediates, we mapped subnucleosomal protections in Drosophila cells using Micrococcal Nuclease followed by sequencing. At the first nucleosome position downstream of the transcription start site, we identified unwrapped intermediates, including hexasomes that lack either proximal or distal contacts. Inhibiting topoisomerases or depleting histone chaperones increased unwrapping, whereas inhibiting release of paused RNAPII or reducing RNAPII elongation decreased unwrapping. Our results indicate that positive torsion generated by elongating RNAPII causes transient loss of histone-DNA contacts. Using this mapping approach, we found that nucleosomes flanking human CTCF insulation sites are similarly disrupted. We also identified diagnostic subnucleosomal particle remnants in cell-free human DNA data as a relic of transcribed genes from apoptosing cells. Thus identification of subnucleosomal fragments from nuclease protection data represents a general strategy for structural epigenomics.